The experience of financial burden for people with multimorbidity: A systematic review of qualitative research. (2nd December 2020) - Larkin, James; Foley, Louise; Smith, Susan M.; Harrington, Patricia; Clyne, Barbara
Abstract: Background: Multimorbidity prevalence is increasing globally. People with multimorbidity have higher health care costs, which can create a financial burden. Objective: To synthesize qualitative research exploring experience of financial burden for people with multimorbidity. Search strategy: Six databases were searched in May 2019. A grey literature search and backward and forward citation checking were also conducted. Inclusion criteria: Studies were included if they used a qualitative design, conducted primary data collection, included references to financial burden and had at least one community‐dwelling adult participant with two or more chronic conditions. Data extraction and synthesis: Screening and critical appraisal were conducted by two reviewers independently. One reviewer extracted data from the results section; this was checked by a second reviewer. GRADE‐CERQual was used to summarize the certainty of the evidence. Data were analysed using thematic synthesis. Main results: Forty‐six studies from six continents were included. Four themes were generated: the high costs people with multimorbidity experience, the coping strategies they use to manage these costs, and the negative effect of both these on their well‐being. Health insurance and government supports determine the manageability and level of costs experienced. Discussion: Financial burden has a negative effect on people with multimorbidity. Continuity of care and an awareness of the impact of financial burden of multimorbidity amongst policymakers and health care providers may partially address the issue. Patient or public contribution: Results were presented to a panel of people with multimorbidity to check whether the language and themes 'resonated' with their experiences.